Barriers and Strategies to Boost Soil Carbon Sequestration in Agriculture - Demenois, Julien; Torquebiau, Emmanuel; Arnoult, Matthieu H.; Eglin, Thomas; Masse, Dominique; Assouma, Mohamed Habibou; Blanfort, Vincent; Chenu, Claire; Chapuis-Lardy, Lydie; Medoc, Jean-Michel; Sall, Saidou Nourou (Frontiers in Sustainable Food Systems, 2020)
The Paris Agreement calls for limiting global warming below 2°C. The “4 per 1,000 Initiative: Soils for food security and climate” was launched in 2015 to increase soil organic carbon sequestration with three objectives: mitigation of climate change, adaptation to climate change and improved food security. One of the challenges of the Initiative relates to its feasibility in contrasted biophysical, social and economic environments, questioning the adoption rate of required new practices. We conducted participatory multi-stakeholder workshops in France and Senegal to collect knowledge and perception of farmers, NGOs, agro-industries, administrations, donors and researchers on barriers and coping strategies for 4 per 1,000 innovations. Results in both countries reveal the predominance of social and economic barriers such as lack of knowledge or training, increased difficulties of fieldwork, workload, risk handling, funding and social pressure. Biophysical constraints such as limited potential of soil organic matter storage or rainfall scarcity and variability appear more important in Senegal. Identified actions to foster the sequestration of soil carbon call for an improved policy context leading to innovations in land planning, stakeholder communication, demonstration facilities, capacity building or financial support. Fewer constraints and coping strategies mention technical issues, showing that fostering agricultural soil carbon sequestration is more a question of enabling environment than technical innovations or farmers' willingness for change. We conclude that actions to support the 4 per 1,000 Initiative need to include a variety of stakeholders such as extension services, private sector, civil society, local institutions, policy makers, consumers, and not only farmers.